2021
DOI: 10.1161/strokeaha.120.032634
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization Focused Analysis of Vitamin D on the Secondary Prevention of Ischemic Stroke

Abstract: Background and Purpose: Experimental studies showed vitamin D (Vit-D) could promote vascular regeneration and repair. Prior randomized studies had focused mainly on primary prevention. Whether Vit-D protects against ischemic stroke and myocardial infarction recurrence among subjects with prior ischemic insults was unknown. Here, we dissected through Mendelian randomization any effect of Vit-D on the secondary prevention of recurrent ischemic stroke and myocardial infarction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…Conversely, there is reasonable evidence that 25(OH)D levels equal or higher than 30 ng/mL reduce the risk of several, multifactorial, and complex diseases [ 59 ]. Nevertheless, our results are supported by genetic mendelian randomized studies [ 60 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Conversely, there is reasonable evidence that 25(OH)D levels equal or higher than 30 ng/mL reduce the risk of several, multifactorial, and complex diseases [ 59 ]. Nevertheless, our results are supported by genetic mendelian randomized studies [ 60 ].…”
Section: Discussionsupporting
confidence: 80%
“…The heterogeneity of the selected studies is caused by differences in the follow-up duration, the different cut-off of 25(OH)D levels and the different definitions of stroke type or outcome. Furthermore, the studies selected for this meta-analysis consider only 25(OH)D levels, without considering nutritional supplementation and solar ultra-violet B exposure, outperformed by genetic mendelian randomized studies [ 46 , 52 , 60 , 61 ]. In turn, the heterogeneity is tempered because three of the selected studies were conducted in the same country (China), and only one enrolled patients from the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most interesting studies are those assessing causality using blood biomolecules as these are easy biomarkers to capture for stroke risk assessment but can also be potential drug targets. Not all the studies to date have observed causal associations with stroke risk, in either direction (inflammatory biomarkers [ 76 , 77 , 79 , 83 ], between circulating cytokines [ 96 ], vitamins [ 78 , 79 , 80 , 81 , 82 , 83 , 114 ], and many polyunsaturated fatty acids [ 70 ]). Some interesting findings are: (1) the identification of a causal link between lower serum MMP-12 levels and the risk of AIS, lower serum MMP-1 and MMP-12 levels and the risk of LAS, and higher serum MMP-8 levels and the risk of SVS [ 94 ]; (2) genetically determined levels of hemostatic factors have also been associated with the risk of IS [ 87 , 88 ]; (3) iron factors are causally associated with an increased risk of IS and CES, except transferrin, which is protective against IS and CES [ 73 ]; (4) among the cytokines studied, monocyte chemoattractant protein-1 (MCP-1) is the only one that was associated with an increased risk of IS, LAS, and CES [ 96 ].…”
Section: Mendelian Randomization In Strokementioning
confidence: 99%
“…Until the present, multiple single-nucleotide polymorphisms (SNPs) have been identi ed at or near loci of genes encoding proteins responsible for Vitamin D transportation (GC, APOA1), biosynthesis (DHCR7, NADSYN1), metabolism (CYP2R1, RRAS2, PDE3B, CYP24A1, CYP27A1, CYP27B1, CYP11A1, SSTR4/FOXA2, AMDHD1, and SEC23A), and activity (VDR and RXRα, RXRβ, RXRγ) (8-12). Around 70 Mendelian randomization analyses have suggested a causal in uence estimation of Vitamin D through genetic variations (13)(14)(15)(16)(17)(18)(19). Detection of common genetic signatures (minor allele frequency (MAF) greater than 5%) that regulate Vitamin D status aids in providing detailed insight into physiological roles and mechanisms and in predicting individuals at risk of Vitamin D de ciency.…”
Section: Introductionmentioning
confidence: 99%